Analisis Pengaruh Kebijakan Dividen, Leverage, dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Konstruksi Dan Bangunan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Anisa Fitria Dhovairy (Jurnal Ilmu Manajemen, 2022)
This study examines the effect of dividend policy, leverage, and profitability on firm value simultaneously and partially in construction and building sub-sector companies listed on the Indonesia Stock Exchange from 2016-to 2020. In contrast to previous studies, this study measures the dividend policy variable with DPR, leverage with DER and DAR, and profitability with ROE. It uses Tobin's Q ratio for the firm value variable. This study uses a quantitative approach. The number of samples in this study is 6 companies from 23 construction and building sub-sector companies in 5 years using the purposive sampling method. Processing research data using multiple linear regression analysis techniques assisted the SPSS 25 program. This study shows that the DPR and DAR have a negative and insignificant effect on firm value (Tobin's Q). DER and ROE have a positive and significant impact on firm value. The construction and building companies are suggested to regard factors that increase the company's value for the shareholders' welfare